2022
DOI: 10.3390/ijms231911713
|View full text |Cite
|
Sign up to set email alerts
|

Study on Biogenic Spindle-Shaped Iron-Oxide Nanoparticles by Pseudostaurosira trainorii in Field of Laser Desorption/Ionization Applications

Abstract: Nanostructures-assisted laser desorption/ionization mass spectrometry (NALDI-MS) is gaining attention for the analysis of a wide range of molecules. In this present investigation, Pseudostaurosira trainorii mediated biosynthesized iron-oxide nanoparticles (IONPs) have been utilized as nanostructures assisting ionization and desorption for laser desorption/ionization mass spectrometry (LDI-MS). The chain forming diatom, P. trainorii showed efficiency in the production of IONPs against 0.01 M Fe+3 (pH 2) aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
2
7
0
Order By: Relevance
“…These results confirmed the presence of Fe atoms, which dominated others in synthesized nanoparticles, pointing towards the highest proportion of Fe 2 O 3 -NPs in the sample. Another study reported a concentration of ultra-filtered Fe 2 O 3 -NPs in suspension, which was in line with our observations [40].…”
Section: Discussionsupporting
confidence: 93%
“…These results confirmed the presence of Fe atoms, which dominated others in synthesized nanoparticles, pointing towards the highest proportion of Fe 2 O 3 -NPs in the sample. Another study reported a concentration of ultra-filtered Fe 2 O 3 -NPs in suspension, which was in line with our observations [40].…”
Section: Discussionsupporting
confidence: 93%
“…To analyse the frustule structure, the identification of functional groups on the surface is important. ATR-FTIR spectra showed a series of bands in the fingerprint region, which according to several reports [ 85 , 90 , 91 , 92 ], indicates bending (445 cm −1 ), symmetrical stretching (805 cm −1 ), and asymmetrical stretching (956, 1075, and 1150 cm −1 ) of the Si–O groups. According to [ 93 ] the vibration in the 565 cm −1 region could be due to the contribution of the siloxane rings.…”
Section: Discussionmentioning
confidence: 59%
“…Strong bands in the 2800–3000 cm −1 regions show stretching of the C–H groups [ 92 ]. Small IR vibrations are visible in the 1670, 1720, and 3660 cm −1 regions and they indicate the presence of the H–O–H deformation, the C = O stretching, and the O–H asymmetric stretching of the Si–OH group, according to several authors [ 85 , 90 , 92 , 94 ].…”
Section: Discussionmentioning
confidence: 79%
“…In order to identify the potential functional groups on the surface of the frustules, ATR-FTIR analysis was performed. According to several reports 12 , 62 , the appearance of strong bands at 1150, 1050, 805 and 442 cm −1 presented asymmetrical stretching, symmetrical stretching, and bending vibrations of Si–O–Si groups, respectively. There are strong bands recognised by several studies 12 , 62 , 63 as C–H stretching at 2981, 2922 (CH 3 ), 2851 (CH 2 ), and 854 cm −1 (Si–(CH 3 ) 2 ), and C=O stretching at 1748 cm −1 .…”
Section: Discussionmentioning
confidence: 71%
“…The widespread use of various organic pollutants, e.g. drugs 10 , antibiotics 11 , phenols 12 , and dyes 13 , in industry has resulted in the problem of water pollution. They are stored as industrial wastes and then purged into environmental water bodies, changing colorless clean water into contaminated colored wastes.…”
Section: Introductionmentioning
confidence: 99%